Environmental risk evaluation of a sanitary landfill using life cycle analysis approach / Farah Ayuni Shafie, Dasimah Omar and Subramaniam Karuppanan. - Shafie, Farah Ayuni; Omar, Dasimah; Karuppanan, Subramaniam (Universiti Teknologi MARA Cawangan Selangor, 2018)
An Environmental Impact Assessment (EIA) auditing was carried out at a sanitary landfill in Kuala Langat, Selangor, Malaysia. It was conducted to assess the environmental and health impact of the landfill. The study also includes an environmental risk index and life cycle analysis (LCA) approach to evaluate the facility. The auditing arrives with a conclusion that this facility might pose a hazard to the environment and health if no adequate control measures are taken consistently. Environmental auditing and LCA simulation could become an essential tool in the monitoring of urban planning and development.